Hesperidin Extracted from Citrus reticulata Blanco Protects Cardiac Mitochondria Against Hypoxia/Reoxygenation Injury - Thu, Vu Thi; Thuong, Phuong Thien (VNU Journal of Science: Natural Sciences and Technology; Vol 37 No 4, 2021)
This study was conducted to evaluate the protective effect of Hesperdin (Hes) extracted from Citrus reticulata Blanco on cardiac mitochondria in hypoxia/reoxygenation (HR) injury in vitro . Methods: H9C2 cardiomyocytes were cultured under normal (control), HR, and treatment conditions. The reactive oxygen species and calcium levels in experimental groups were analyzed by using suitable fluorescence kits. Results: The obtained results showed that the addition of Hes at dose of  0,01562 mg/mL sharply decreased the mitochondrial oxidative stress of H9C2 cells under HR conditions. In particular, Hes showed the remarkable efficiency in maintaing cellular calcium levels. In HR-exposed H9C2 cell group, the hydrogen peroxide and superoxide levels were highly increased compared to those in control group (1,54±0,06 and 1,74±0,38, p<0,05). HR also strongly induced the elevation of cytosolic Ca²⁺ and mitochondial Ca²⁺ of H9C2 cardiomyocytes with the values were 1,96±0,05% and 1,62±0,33 (ratio to control, p<0,05), respectively. Interestingly, post-hypoxic supplementation of Hes effectivelly abolished the negative incresement of these indicators with the lower levels of reactive oxygen species and the better modulation of Ca²⁺ homeostasis. Conclusion: The present results are pilot data on the effects of Hes in protecting cardiac mitochondria against HR injury.